2004
DOI: 10.1073/pnas.0403155101
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Arabidopsis myosin XI mutant is defective in organelle movement and polar auxin transport

Abstract: Myosins are eukaryotic molecular motors moving along actin filaments. Only a small set of myosin classes is present in plants, in which myosins have been found to play a role in cytoplasmic streaming and chloroplast movement. Whereas most studies have been done on green algae, more recent data suggest a role of higher plant myosin at the postcytokinetic cell wall. Here we characterize a loss-of-function mutation for a myosin of plant-specific class XI and demonstrate myosin functions during plant development i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 47 publications
3
43
1
Order By: Relevance
“…This pattern of filament rearrangement is different from that following treatment of etiolated coleoptiles with auxin or light, which also were visualized with a GFP-talin construct (Holweg et al, 2004). Whereas both light and Glc treatments cause a loss of fine mesh filaments, light treatment in the study by Holweg et al (2004) resulted in the realignment of actin into dispersed longitudinal strands that lack the extensive bundling that we observed following short-term Glc treatment. We further have shown that long-term Glc treatment that causes arrested seedling development resulted in further alterations in F-actin organization.…”
Section: Discussionmentioning
confidence: 55%
“…This pattern of filament rearrangement is different from that following treatment of etiolated coleoptiles with auxin or light, which also were visualized with a GFP-talin construct (Holweg et al, 2004). Whereas both light and Glc treatments cause a loss of fine mesh filaments, light treatment in the study by Holweg et al (2004) resulted in the realignment of actin into dispersed longitudinal strands that lack the extensive bundling that we observed following short-term Glc treatment. We further have shown that long-term Glc treatment that causes arrested seedling development resulted in further alterations in F-actin organization.…”
Section: Discussionmentioning
confidence: 55%
“…The fastest, among known molecular motors, processive motion supported by myosin XI-2 ortholog from Nicotiana benthamiana suggested that it might play a role in cytoplasmic streaming (Tominaga et al, 2003). It was also reported that inactivation of the XI-2 (same as MYA2) gene in Arabidopsis resulted in a slower movement of certain vesicles and severe developmental abnormalities (Holweg and Nick, 2004). However, because two independent studies, including an accompanying article (Peremyslov et al, 2008), failed to reproduce the latter phenotype (Hashimoto et al, 2005), its significance remains unclear.…”
mentioning
confidence: 98%
“…Subsequently, such auxin-enriched vesicles act as carriers for the quantal release of auxin by means of exocytosis in a neurotransmitter-like mode [15,17]. In accordance with this 'neuronal' concept of auxin export, defects in vesicle trafficking in a myosin XI mutant of Arabidopsis are accompanied by failures of the basipetal auxin transport [38].…”
Section: Box 1 Molecules and Transmitters Of Plant Synapsesmentioning
confidence: 67%